G354(P) Health for all children 5: a comprehensive critical review of evidence supporting child health programmes. (May 2019) - Emond, A; Adams, C; Barlow, J; Bedford, H; Blair, M; Cowley, S; Elliman, D; Hunter, L
Abstract : Background: The first edition of 'Health for All Children' (HFAC) in 1989 was the result of a BPA working party chaired by David Hall, and set out an evidence-based programme of screening and surveillance for children. The book became known as the 'Hall report' and the RCPCH supported 3 subsequent revisions, with the last being published in 2006. A new edition is needed because the evidence base has expanded, the commissioning landscape has changed, and the child health programmes in different UK nations are diverging. Aim: To provide an up-to-date concise review of evidence supporting child health programmes to inform commissioners and support practitioners. Methods: In 2015, the RCPCH and Oxford University press (OUP) established a multidisciplinary editorial group to undertake a comprehensive critical review of evidence supporting child health from all over the world, and make recommendations for the UK. A weighting of the strength of the evidence is attached to each recommendation. Results: HFAC 5 reviews the evidence supporting preventive health care, health promotion and an effective community-based response to the needs of families and children, from pregnancy to age 7. The philosophy is to improve child health by reducing inequalities through a programme of proportionate universalism, with enhanced and targeted services for families with extra needs. This book summarises evidence about 'why' and 'what works' in health promotion and health surveillance with children and families, where possible gives guidance on 'how' to implement and quality assure a programme –but does not conclude on 'who' should provide the service. Recommendations are made for commissioners of child health services, provider organisations and Trusts, and practitioners. The strength of recommendations is determined by the balance between the quality of evidence, variability in values and preferences, desirable and undesirable consequences of alternative strategies, and resource use. HFAC 5 has 35 chapters divided into 6 sections. Each chapter concludes with 'learning links': recommended e-learning courses and online materials to support evidence -based practice Conclusions: HFAC 5 is available as an e-book and a paperback published by OUP, and on Paediatric Care Online.